The Selection of Thermistors for the Temperature Measurement Gear - Leskauskaite, J.; Dumcius, A. (Elektronika ir Elektrotechnika, 2011)
The parameters represented on manufacturer datasheet are usually insufficient for the optimum selection of thermistors. Some manufacturers give generalized numerical data of R(T) dependences. Using this data it is possible to select successfully the most suitable thermistor and equation for describing of T(R) dependence. It is shown that by selecting four points in the generalized characteristic it is possible to calculate the coefficients of the approximation equation. By the application of these coefficients in the calculations the temperature measurement errors can be decreased by an order. The results of calculations and experiment are given. Ill. 4, bibl. 8, tabl. 5 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.357